In response to ‘Mastectomy under Local Anesthesia in Locally Advanced Breast Cancer in an Unfit Patient (Bangladesh Journal of Medical Science, 2024)
Abstract not availableBangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 276-277